2016
DOI: 10.1103/physrevlett.117.144103
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Breather Dynamics in Irregular Sea State Conditions

Abstract: Breather solutions of the nonlinear Schrödinger equation (NLSE) are known to be considered as backbone models for extreme events in the ocean as well as in Kerr media. These exact determinisitic rogue wave (RW) prototypes on a regular background describe a wide-range of modulation instability configurations. Alternatively, oceanic or electromagnetic wave fields can be of chaotic nature and it is known that RWs may develop in such conditions as well. We report an experimental study confirming that extreme local… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 48 publications
(46 reference statements)
3
39
0
Order By: Relevance
“…Presence of the PSs in the spatiotemporal evolution of the partially-coherent wave in the 1-D focusing NLS governed systems is an experimentally verified fact [27][28][29]. However, the modulation instability cannot be considered as a dominating mechanism in this case.…”
Section: Introductionmentioning
confidence: 96%
“…Presence of the PSs in the spatiotemporal evolution of the partially-coherent wave in the 1-D focusing NLS governed systems is an experimentally verified fact [27][28][29]. However, the modulation instability cannot be considered as a dominating mechanism in this case.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, the effectiveness of the PB for modeling rogue waves in random seas depends on whether it can persist in such situations. More recently, it is confirmed in both laboratory and by weakly nonlinear numerical simulations that the PB is able to persist in random seas [14], which means that the PB can also be adopted for modeling rogue waves in irregular seas. Subsequently, Klein, et al [15] successfully reproduced the New Year Wave in laboratory by embedding the PB into RBW, and good agreement was achieved.…”
mentioning
confidence: 54%
“…The experiments are in a very good agreement with the fully nonlinear BEM-based NWT2D simulations with a spatial resolution of 2.5 cm while NLS provides a solid predicting power to study these higher-order breathers in a given hydrodynamic environment. Future work will be devoted to studies of the limitations of the theory of higherorder ABs when applied to the water surface as well as their applicability to realistic oceanic conditions following an example of Chabchoub (2016). Furthermore, the choice of NWT2D resolution in the analysis of steep nonlinear waves needs further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…When studying the MI in laboratory environments, it turns out that breather description can be very useful when considering the excitation of extreme events (Dudley et al 2009;Kibler et al 2010;Chabchoub et al 2011Chabchoub et al , 2014. Lately, it has been shown that breathers can indeed persist in sea state configurations (Chabchoub 2016), thus, proving its importance in the study of unidirectional extreme seas. Furthermore, recent studies also emphasized the significance of these pulsating solutions for sea keeping tests as well as for developing standards for ships and marine offshore structures (Bitner-Gregersen and Gramstad 2015).…”
Section: Introductionmentioning
confidence: 99%